Redefining student voice: applying the lens of critical pragmatism. (3rd September 2022) - Jones, Mari-Ana; Hall, Valerie
ABSTRACT: During the past thirty years, student (or pupil) voice has gained attention in education policy especially in many Western countries, accelerated by both the acceptance of the United Nations Convention on the Rights of the Child (UNCRC) in 1990 and an emphasis on accountability in schools. Multifaceted and complex, student voice in schools incorporates a wide variety of practices associated with children expressing their views about their education. This article traces the evolution of the concept of student voice in schools over the past three decades, exploring how various understandings have impacted on practice. Using this historical perspective as a springboard, the article suggests a different approach to the practice of student voice in schools: as interwoven with, and integral to practice. Neither an accountability measure, nor a tokenistic rehearsal of democratic processes, the lens of critical pragmatism is utilised to argue that student voice can only be given meaning as an integral part of everyday critically reflexive practice.